GAMBARAN STATUS GIZI SISWA PUTRI KELAS II SMP PATRA DARMA BALIKPAPAN - nina mardiana; Wiryanto Wiryanto (MNJ (Mahakam Nursing Journal), 2016)
Abstract East Kalimantan province, including 19 provinces with a prevalence of underweight children of school age (women) above the national prevalence, the national prevalence of underweight children of school age (women) was 10.9%. Nutritional problems in adolescents arise because of the wrong nutritional behaviour, namely the imbalance between nutritional intake with the recommended dietary allowance. A group of teens need to consume a lot of food if the food is not balanced with the need calories for growth and development, there will be a deficiency that could eventually hamper its growth. This study aims to give a picture of the Nutritional Status of Young Women Class II SMP Patra Dharma I Balikpapan. The results of this study were 9 people (19.1%) of young women students of class II SMP Patra Dharma I Balikpapan are in the category of thin, 13 people (27.7%) arm circumference of less than 23.5 cm, the average height between 145.46 to 147.31 cm, and the mean hemoglobin levels between 8.61 to 11.80 g%. The conclusion of this study the nutritional status of adolescent girls class II SPM Patra Darma I Balikpapan still low so it needs strict supervision of parents in terms of healthy eating and giving young women iron tablets. Keywords: Nutritional status of young women, SMP Patra Dharma.